Comparison of Tension-free Vaginal Tape Versus Transobturator Tape in Women with Stress Urinary Incontinence - Zinat Ghanbari (Journal of Family and Reproductive Health, 2007)
Objective: This study compared the Tension-free vaginal tape (TVT) and Transobturator tape (TOT) procedures for surgical treatment of stress urinary incontinence in women. Materials and methods: This prospective non randomized clinical trial was conducted in Vali-e-asr hospital from March 2001 to March 2005. A total of 71 patients with clinical and urodynamic diagnosis of Stress urinary incontinence (SUI) were enrolled in the study. Patients were divided into two groups and underwent TVT or TOT procedures. Mean operation time, cure rate, post  operative urinary retention, bleeding and infection were compared between two groups. SPSS software was used for statistical analysis. Chi square and fisher exact test calculated the effects of the nominal variables. Mean difference of quantitative variables were compared by student's T- test. P ≤0.05 was considered statistically significant. Results: There was no significant difference in mean time of operation and peri-operative complications among groups. Urinary retention was 13.8% (n=5) in the TVT group versus 2.8% (n=1) in TOT group (NS). The rates of cure (91.6% vs 91.4%), improvement (5.6% vs 8.6%) and failure (2.8% vs 0) were similar for the TVT and TOT groups. The rate of hemorrhagic complications was 5.5% in TVT and 2.8% in TOT group (NS). Conclusion: TOT appears to be equally efficient to TVT for  surgical treatment of stress urinary incontinence after 30 months follow-up.